Perlindungan Hukum Merek Terkenal Terhadap Tindakan Pemboncengan Reputasi di Indonesia: Studi Yuridis - Laurene Patricia; Wilma Silalahi (Dinasti Research, 2024)
Although laws regulating trademark protection exist, dynamic business practices often create legal risks, particularly in cases of passing off well-known trademark. This practice involves third parties unlawfully exploiting the image of a brand without permission, potentially infringing on the owner's exclusive rights and misleading consumers with counterfeit products. Consequently, the reputation of a brand built over many years can become tarnished, leading to financial and reputational losses for the owner. This research aims to analyze the legal protection mechanisms against passing off well-known trademark in Indonesia. The methodology employed is normative legal research with a legislative approach, utilizing primary data from regulations and secondary data from legal literature. Through qualitative analysis, this study provides an understanding of how laws are interpreted and applied, as well as identifying the strengths and weaknesses of existing regulations in protecting well-known trademark from passing off.